Analytical Method Development of Process Related Impurities of drug Lacidipine by using RP HPLC Techniques - Bendre, Suraj Daulatrao; Jaiswal, Shikha; Kumar Jain, Sachin; Vengurlekar, Sudha (Journal of Neonatal Surgery, 2025)
The synthesis and Retro synthesis of Lacidipine was studied to determine the process-related impurities in Lacidipine formulation. The intermediates of the drug treated as impurities were decided and planned for the synthesis. General Method for 1,4dihyropyridine Synthesis was used. The purity of the intermediate was carried out by column chromatography using dimethyl sulfoxide (DMSO) as mobile phase. The technique was observed to be explicit, direct, delicate, exact and precise. The outcomes showed great middle of the road accuracy. Versatile stage stream rate seemed to have critical impact on power, and thus it was essential to be painstakingly controlled.